Comprehensive analysis of ionomic profiling in Chlorella exposed to chlorpyrifos - Qing-Qing Yu; Yulong Zhang; Shiyuan Zhao; Min Pang; Pei Jiang; Pei Qu (Frontiers in Marine Science)
IntroductionChlorpyrifos (CPF), a widely used organophosphorus insecticide, is highly toxic to non-target aquatic organisms and has relatively high persistence in water, posing a serious threat to marine ecosystems. However, little is known about the toxicological mechanism of CPF on marine microalgae, which is the main primary producer in the marine ecosystem.MethodsThis study explored the ion changes of microalgae Chlorella vulgaris under the stress of CPF through Inductively Coupled Plasma Mass Spectrometry (ICP-MS).ResultsSignificant disparities in ionomics among control and treatment group were observed through pattern recognition analysis (principal component analysis, PCA; orthogonal partial least squares discriminant analysis, OPLS-DA), indicating that CPF may impede their growth by disrupting the homeostasis of crucial elements within algal cells.DiscussionThis study elucidated the inhibitory impact of CPF on green algae growth and its potential mechanism of toxicity through ICP-MS, providing crucial insights for a comprehensive understanding of the influence of organophosphorus pesticides on aquatic ecosystems.